Adverb Clause Analysis in Dependent Clause of Complex Sentence Case Study Bali Travel News - Pramudya Dyah Putranti; Putu Devi Maharani; Ni Made Verayanti Utami (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
Abstract This study aims to identify the types of adverb clause in dependent clause of complex sentence and the constituent structure of complex sentence. The data were taken from five edition in Bali Travel News Newspaper. Observation and note taking were used in collecting the data. This study used descriptive and qualitative method for analyzing the types of adverb clause and the constituent structure of complex sentences. The data were analyzed based on theory proposed by Oshima and Hogue (2006) to identify the types of adverb clause in dependent clause of complex sentence and theory proposed by Brown and Miller (1991) to analyze the constituent structure of complex sentences. The result of this study shows that there are five types from eleven types of adverb clause that found, those are adverb time clause, adverb reason clause, adverb concession clause, adverb direct opposition clause, and adverb conditional clause. Adverb time clauses are the most commonly used in Bali Travel News Newspaper with number percentage was (33,3%), followed by adverb reason clauses are (27,8%), (16,7%) for adverb concession clauses and adverb conditional clauses, and (5,5%) for adverb contrast clauses. Hierarchical tree diagram is used to describe the constituent structure of the data.